ChemInform Abstract: Pd(II)‐Catalyzed Aerobic Oxidation Intramolecular Hydroamination and C—H Functionalization of N‐Alkynyl Anilines for the Synthesis of Indole Derivatives. Issue 41 (19th September 2013) - Ren, Long; Shi, Zhuangzhi; Jiao, Ning
Abstract Optimized conditions allow the selective preparation of pyrroloindole derivatives (II) with the exception that halo‐substituted substrates (III) give pyrroles (V) as side products.